2014
DOI: 10.3938/jkps.64.1886
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a 600-V/20-A 4H-SiC schottky barrier diode

Abstract: were 0.7% and 8.9% and that blocking voltage was enhanced. This is attributed to a stabilized interface between passivation layer and SiC that is caused by aging.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Data are taken from Refs. [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Figurementioning
confidence: 99%
“…Data are taken from Refs. [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Figurementioning
confidence: 99%
“…Indium phosphide (InP) is an important III-V material due to its electronic and optoelectronic device applications, such as solar cells, laser diodes, photodetectors, HEMTs, high-speed metal insulator semiconductor field-effect transistors, microwave sources and amplifiers operating at high power and high frequencies [22]. The major discrepancy in using an n-InP substrate for Schottky junctions arises due to high surface states and nonstoichiometric defects, which results in lower height value (<than 0.5 eV) of Schottky barrier [23] and a high reverse leakage current [24].…”
Section: Reviewmentioning
confidence: 99%
“…Indium phosphide (InP) is an important III-V material due to its electronic and optoelectronic device applications, such as solar cells, laser diodes, photodetectors, HEMTs, high-speed metal insulator semiconductor field-effect transistors, microwave sources and amplifiers operating at high power and high frequencies [22]. The major discrepancy in using an n-InP substrate for Schottky junctions arises due to high surface states and nonstoichiometric defects, which results in lower height value (<than 0.5 eV) of Schottky barrier [23] and a high reverse leakage current [24].Cetin and Ayyildiz [25] first studied the electrical properties of a MOS Schottky diode fabricated on an InP substrate and showed that Cu/n-InP and Al/n-InP Schottky barrier diodes with and without the interfacial oxide layer were fabricated.Native oxides have great importance in the passivation of the InP surface. Wolan and Hoflund [26] investigated these native oxides on the InP surface and found that oxides, such as In(PO 3 ) 3 condensed phosphates, can lead to MOS Schottky devices with low interface state density.…”
mentioning
confidence: 99%
“…Based on this explanation, the leakage current for the inhomogeneous interface could be lower than the homogeneous interface because less current can flow through the barrier due to a high activation requirement. Kang [27] in his paper cited that a Schottky diode may exhibit a large leakage current, regardless of having a good ideality factor and the absence of an interface crystal defect.…”
Section: Electrical Characterizationmentioning
confidence: 99%